Critical success factors of quality management for the Singapore shipping industry - Lu, Jixizi (2015)
Quality Management (QM) is often advocated as a solution to revive a troubled business or to attain a competitive edge over rivals. The Singapore shipping industry is a crucial industry to the nation's economy but with recurring and new challenges, it has to progress continuously by incorporating QM into the organizations’ systems and values. However, QM is not a one-size-fits-all initiative but rather, requires thorough understanding and design to best suit the company and its environment. In view of the inadequate studies on the critical success factors (CSFs) of QM in Singapore's shipping industry, this research aims to (1) examine the significance of QM to organisations, (2) explore and identify the specific CSFs of QM under three broad categories, (3) measure and justify the extent of current quality practice, (4) investigate the impact of CSFs on key performance indicators such as customer and employees' satisfaction, (5) derive the interdependency among the CSFs. Drawing from SPRING Singapore's Business Excellence framework and prior studies, three categories of CSFs were identified -- Top Management, Process, and People. Quantitative surveys and qualitative interviews were then carried out to evaluate the respective CSFs for the aforementioned objectives. Thirty-one companies were surveyed and six representatives of varying perspectives were interviewed. The data collated was then analysed to derive insights on the topic. The factors under the three categories are highly practiced by the responding organisations, implying about their relevance and significance to the overall QM implementation. However, not all factors are equally emphasized. Many of them are affected by other independent variables such as company size and operation scopes. Surprisingly, top management CSFs did not have casual relationship with customer satisfaction, while it was proven to exist for all the other identified CSFs. However, it was later found that they do have an indirect impact on customer satisfaction via increased employee satisfactions. Discrepancies were present and we concluded that it could have been due to the small sample size, invalidity of assumptions, or biased perception. The interviews conducted further substantiated the initial hypothesized relationship, thus complementing the loopholes in the statistical surveys. Future research study could focus on the impact of the identified factors for specific shipping sectors, attaining larger survey and interview samples, as well as conducting focus group and case studies to examine the interdependency of these factors in greater empirical details.